PENGARUH KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PERKEBUNAN KABUPATEN MUSI RAWAS - Suwarno Suwarno (LPPM UNIVERSITAS BINA INSAN, 2017)
The purpose of this study was to determine the effect of communication and leadership on employee performance at the Plantation Office of Musi Rawas Regency. Based on the regression equation: Y = 98,008 + 0,256 X1 + 0,158 X2 From equation constant value equal to 98,008 which mean if there is no communication variable then performance equal to 98,001, whereas value of coefficient of regresi of leadership variable equal to 0,256 meaning every increase one unit of leadership will improve employee performance by 0.158 units. Based on the calculation of the correlation coefficient, it can be seen that the value of R is 1.169 passing the value 1, which means that communication relationships, leadership and employee performance at the Plantation Office of Musi Rawas Regency strong, this means that if the level of communication and leadership does not increase it will decrease employee performance at the Plantation Office of Musi Rawas Regency, and vice versa if the level of communication and leadership increases it will improve the performance of employees at the Plantation Office of Musi Rawas Regency. Result of calculation of equal to 0,029, this means that performance variable influenced by variable of communications and leadership variable. The rest is influenced by other factors not examined in this study. Based on F test result, it is obtained F value = 19,76> F table 3,44, this means Ho is rejected and Ha accepted, meaning that communication variable (X1) and leadership (X2) is the factor affecting employee performance (Y) in Dinas Perkebunan Regency of Musi Rawas. One of the motivators to achieve the goal of Plantation Office of Musi Rawas Regency is to improve the performance of its employees.